Analisis Kebutuhan Bahan Ajar pada Mata Kuliah Anatomi Tumbuhan - Muliana GH; Andi Citra Pratiwi (Peneliti.net, 2023)
The purpose of this study was to analyze student needs for teaching materials in plant anatomy courses. This research is a descriptive qualitative research with research subjects being students majoring in biology in science class in the third semester consisting of 32 students. Data collection was carried out by distributing questionnaires for plant anatomy course teaching materials to respondents, in this case students who were programming plant anatomy courses. The data analysis technique is by describing the results of the questionnaire data for student teaching materials in plant anatomy courses in detail. The results of this study are: 1). Learning resources that are generally used by students in the plant anatomy lecture process are sourced from lecturer power point slides, 2). The types of teaching materials needed/desired by students are generally in the form of textbooks on plant anatomy, 3). Sub-chapter material in the course that is easy for students to understand is meristem tissue, parenchyma tissue, collenchyma tissue and sclerenchyma tissue, 4). Sub-chapter material in plant anatomy courses that students find difficult to understand is xylem and phloem tissue. This research is expected to be a reference for the development of teaching materials and the development of learning media in plant anatomy courses.